Sustainable Urban Planning: Policy Approaches to Disaster Risk Reduction and Environmental Impact Mitigation in Makassar City - A.M. Azhar Aljurida; Anirwan Anirwan (Universitas Pancasakti, 2026)
The urgency of this research stems from the escalating risks of flooding and air pollution in Makassar City, driven by rapid urbanisation and the uncontrolled proliferation of motorised vehicles. The study aims to examine the potential of urban planning and sustainable mobility policies in mitigating disaster risks and environmental impacts, as well as to formulate more adaptive policy strategies. A qualitative research design was employed, with data collected through in-depth interviews, document analysis, observation, and focus group discussions (FGDs). Data analysis was conducted using NVivo 12 Plus. The findings confirm that Makassar City faces severe ecological vulnerability as a result of the interplay between rapid urbanisation, land-use conversion, inadequate drainage infrastructure, and the extraordinarily high growth rate of motorised vehicles. These factors collectively contribute to annual flooding, air pollution, and the urban heat island effect. The situation reveals significant weaknesses in spatial planning and transportation policies, which remain predominantly oriented toward economic growth and have yet to be fully integrated with climate change adaptation principles. Furthermore, these policies are characterised by insufficient inter-agency coordination and limited community participation. Accordingly, policy strategies that prioritise green infrastructure development, drainage system revitalisation, environmentally sustainable public transportation, and climate-adaptive urban planning are identified as urgent imperatives for the resilience and long-term sustainability of Makassar City. In conclusion, climate-adaptive and sustainable urban planning constitutes a critical precondition for reducing disaster risk and preserving environmental quality in Makassar City.